Letter from editor (2013)
Find available in your hands or just a click far this new number of the Earth Sciences Research Journal. It has been the product of a hard work not only for the authors but also for all people related to this project. During 17 years we have been here struggling for being a bridge between all scientific world in our knowledge fields. It has been not easy but we are here and we will be here for long time now.A project of a scientific journal, located in a country as Colombia and aimed to contribute in the entirely world as source of first quality information, hand in hand with so many publications in countries with a better development index, its a titanic task which just be earned thanks to all of you, readers, authors, contributors, critics, reviewers, staff workers.Our country currently is planning a new characterization of journals as this one you are reading now. Thanks to our tiredless work now we can warrant to every one of our users than we are going to keep our category as a journal of first quality. But we need your support.As part of our compromise this time we offered important papers in the development of the Earth Sciences which we are completely sure are necessary in the current state of art.Our first article in this number come from the Persian Gulf with an intelligent model based in probabilistic neural networks to produce a quantitative formulation between seismic attributes and hydraulic flow units. Based on the results of this study the exploration success rate and the costs reduction would be improved through the application of more reliable output results in hydrocarbon explorations programs.As it has been traditionally in our journal, an important percentange of the papers are related to hydrogeology studies. From different countries, we present four papers analyzing groundwater potential zonation, psychochemical characteristics, spatio-temporal variability of an aquifer in Iran and nutrients loads in drainage water from a costal irrigated area. Other manuscript is an evaluation of the forecasting performance of two nonlinear models using stream flow data of the Kızılırmak River, the longest one in Turkey.In seismology two importants submissions deploy, in one hand, an analysis of the Rayleigh-wave ellipticity to determine the local crustal structure (based in Spain) and an analysis of two-dimensional principal components during the earthquake which took place in Papua New Guinea on 7 July 2013, in the other hand.From Colombia an important group of metamorphic rocks were studied to obtain the pressure-temperature conditions in a petrogrpahic analysis from mineral assemblages which indicated a prograde regional metamorphism.We close this edition with important works in ore deposits and geotechnics coming from LatinAmerica and Turkey.Finally we want to thank to the reviewers who have made possible this volume.Carlos A. VargasEditor